2017
DOI: 10.1007/s11248-017-0047-9
|View full text |Cite
|
Sign up to set email alerts
|

High accumulation in tobacco seeds of hemagglutinin antigen from avian (H5N1) influenza

Abstract: Tobacco seeds can be used as a cost effective system for production of recombinant vaccines. Avian influenza is an important respiratory pathogen that causes a high degree of mortality and becomes a serious threat for the poultry industry. A safe vaccine against avian flu produced at low cost could help to prevent future outbreaks. We have genetically engineered tobacco plants to express extracellular domain of hemagglutinin protein from H5N1 avian influenza virus as an inexpensive alternative for production p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 83 publications
0
9
0
Order By: Relevance
“…While examples of plant-produced enveloped virus vaccine candidates can be found from a wide variety of enveloped virus families, the only examples of products clinically tested in humans to date are hepatitis B virus [ 18 , 20 ], influenza virus [ 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ], and SARS-CoV-2 [ 70 ]. There have, however, been numerous pre-clinical trials in animal models, and some trials of potential veterinary vaccines in target animals [ 54 , 64 , 102 , 165 , 191 ]. While examples of plant-produced enveloped VLPs are comparatively rare compared to non-VLP subunits or non-enveloped VLPs, they are clearly over-represented in the clinical trials carried out in humans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While examples of plant-produced enveloped virus vaccine candidates can be found from a wide variety of enveloped virus families, the only examples of products clinically tested in humans to date are hepatitis B virus [ 18 , 20 ], influenza virus [ 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ], and SARS-CoV-2 [ 70 ]. There have, however, been numerous pre-clinical trials in animal models, and some trials of potential veterinary vaccines in target animals [ 54 , 64 , 102 , 165 , 191 ]. While examples of plant-produced enveloped VLPs are comparatively rare compared to non-VLP subunits or non-enveloped VLPs, they are clearly over-represented in the clinical trials carried out in humans.…”
Section: Discussionmentioning
confidence: 99%
“…In these and other studies, protein accumulation was improved by the removal of the HA transmembrane domain (TM) and/or ER retention without compromising immunogenicity or efficacy in animal models [ 48 , 49 , 50 , 51 , 52 , 53 ]. While expression has mainly been achieved through transient expression in Nicotiana leaves, expression of immunogenic HA in tobacco seeds was also shown to be possible [ 54 ], as was the expression of influenza nucleoprotein in maize seeds [ 55 ]. The numerous successes in animal models supported the clinical development of some of the subunit HA candidates described above, with two phase 1 trials reported [ 56 , 57 ].…”
Section: Influenza Virusesmentioning
confidence: 99%
“…In a review paper, Redkiewicz et al summarized the results achieved from different plant expression systems for the production of HA [91]. Here, we will only mention some of the latest results achieved by stable expression of HA: avian H5N1 HA was found to be stably expressed in tobacco seeds [92] with a yield of 3.0 mg of the viral antigen per g of seed; and H3N2 nucleoprotein was detected in transgenic maize with a yield of 35 µg of NP/g seed [93]. The relatively low levels of recombinant protein accumulation in stable transgenic plants indicate that transient expression is more promising for developing an influenza vaccine in plants.…”
Section: Influenza Virusesmentioning
confidence: 99%
“…Whereas 6 months or more is needed to prepare sufficient quantities of egg‐derived vaccine to meet global demand, the same can be achieved in plants within a few weeks (Shoji et al ., 2012 ), as proven in the abovementioned DARPA Blue Angel program that produced 10 million doses in one month (Lomonossoff and D’Aoust, 2016 ). For this reason, although some influenza antigens have been produced in transgenic plants (Ceballo et al ., 2017 ; Firsov et al ., 2015 ; Lee et al ., 2015 ), most have been transiently expressed in N. benthamiana (Hodgins et al ., 2017 ; 2019a , b ; Landry et al ., 2014 ; Shoji et al ., 2009a , b ; Shoji et al., 2013 , 2015 ; Table S1 ) including all vaccine candidates intended for commercial development. Several products indicated for seasonal and pandemic influenza have already reached late‐stage clinical development, including vaccines against novel influenza strains and quadrivalent vaccines against seasonal variants (Chichester et al ., 2012 ; Cummings et al ., 2014 ).…”
Section: Molecular Farming As a Strategy To Address Rapidly Spreading Epidemic And Pandemic Diseasesmentioning
confidence: 99%